Preferences for the research use of electronic health records among young adults with fragile X syndrome or autism spectrum disorder. Issue 4 (October 2020) - Wagner, Laura; Frisch, MaryKate; Turner-Brown, Lauren; Andrews, Sara; Edwards, Anne; Moultrie, Rebecca; Alvarez Rivas, Alexandra; Wheeler, Anne; Raspa, Melissa
Abstract: Background: Health researchers are increasingly using electronic health records (EHRs) to study the health care needs of people with neurodevelopmental disorders (NDDs). However, little is known about the preferences of people with NDDs for sharing EHRs for research. Objective: To explore preferences for sharing EHRs for research among young adults ages 18–40 who make their own legal decisions and who have autism spectrum disorder (ASD), fragile X syndrome (FXS), or no NDDs. Methods: We conducted a qualitative study with seven focus groups: 2 ASD groups, 3 FXS groups, and 2 no-NDD groups. We asked participants about factors that could affect their willingness to share their EHRs for research: type of organization, type of information, study purpose, duration, contact frequency, return of results, benefits, and risks. We analyzed the qualitative data using directed content analysis. Results: Participants with NDDs valued personally relevant and directly beneficial EHR research. Participants with NDDs expressed willingness to share sensitive data if the study was personally relevant. Most participants wanted to receive results, but only participants with FXS indicated it would affect their willingness to participate. Participants were concerned about privacy risks, discrimination, researcher misconduct, and financial conflicts of interest. Conclusion: This study provides initial evidence suggesting that young adults with NDDs prefer EHR research that is personally relevant, benefits themselves and their communities, and is conducted in the context of trusting, reciprocal participant-researcher relationships. The findings point to the need for researchers to improve the informed consent process and to better engage individuals with NDDs in research.